PENGARUH PENDAPATAN ASLI DAERAH, SIZE, DAN LEVERAGE TERHADAP PERTUMBUHAN EKONOMI PADA KABUPATAEN/ KOTA DI PROVINSI SUMATERA UTARA - Junita Putri Rajana; Debby Chyntia Ovami (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2019)
Economic growth is one of succesful indicator of development success. Increase the economy can measure the level of development in the economic sectors in the country, include large countries. To increase economic growth in one area, both government and investors need to look things that can increase economic growth, like: local revenue (PAD), size, and leverage. This study aims to determine and analyze the influence of the local revenue (PAD), size and leverage simultaneously and partially on economic growth in the cities of North Sumatra Province. This research is descriptive quantitative by researching all cities of North Sumatra Province. The data used is secondary data obtained from the cities's APBD report in North Sumatra for 2011-2015. By using a quantitative approach and data analysis using multiple linear regression models. The Outreach target in this study is the ISSN journal. Specific target in this research is nationally organized ISSN events. After the results are processed there will be a significant effect from PAD, Size and Leverage on Economic Growth in the Citiesof North Sumatra Province.